Son of Stone : a Stone Barrington novel - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2011)
" A new addition to the New York Times-bestselling Stone Barrington series. After an eventful trip to Bel-Air and a reunion with his sophisticated (and very wealthy) former love, Arrington Calder, Stone Barrington is back in New York, and he's looking to stay closer to home and cash in on his partnership at Woodman & Weld. But Arrington has other plans for Stone...including introducing him to the child he fathered many years ago"--